2006
DOI: 10.1121/1.2151806
|View full text |Cite
|
Sign up to set email alerts
|

Perception and production of English vowels by Mandarin speakers: Age-related differences vary with amount of L2 exposure

Abstract: In this study we assessed age-related differences in the perception and production of American English (AE) vowels by native Mandarin speakers as a function of the amount of exposure to the target language. Participants included three groups of native Mandarin speakers: 87 children, adolescents and young adults living in China, 77 recent arrivals who had lived in the U.S. for two years or less, and 54 past arrivals who had lived in the U.S. between three and five years. The latter two groups arrived in the U.S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
88
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(98 citation statements)
references
References 39 publications
9
88
0
1
Order By: Relevance
“…that the words in a second language are considered to be noisy in late learners, and this point should be taken as an interpretation of our computational results. In fact, as pointed out by one of the reviewers, many studies have concluded that the amount and variability of second language input [68]–[70] as well as the frequency of using the native language during learning [71] have considerable influence in the age of acquisition effects.…”
Section: Resultsmentioning
confidence: 99%
“…that the words in a second language are considered to be noisy in late learners, and this point should be taken as an interpretation of our computational results. In fact, as pointed out by one of the reviewers, many studies have concluded that the amount and variability of second language input [68]–[70] as well as the frequency of using the native language during learning [71] have considerable influence in the age of acquisition effects.…”
Section: Resultsmentioning
confidence: 99%
“…In a similar vein, Flege and colleagues (1995) showed that, other than age of acquisition, length of English use may account for up to 15% of the total variance on the perceived severity of L-ESL listeners' non-native accent. Furthermore, length of English use in, or consistent exposure to, an English-dominant environment, has also been suggested to significantly affect ESL listeners' speech perception (Flege et al, 1996;MacKay et al, 2001;Jia et al, 2006). Thus, studies focused on ESL listeners should evaluate a collection of linguistic factors to better account for variance in these listeners' perception and production of English speech (von Hapsburg & Peñ a, 2002).…”
Section: Sumariomentioning
confidence: 98%
“…PAM-L2 focuses on learners who are actively acquiring their L2, and identifies factors that are important in the formation of L2 speech categories (Best & Tyler, 2007). For instance, the contribution of age of L2 learning is modulated by the relative quantity and quality of input from native L2 speakers (Flege & Liu, 2001, Jia & Aaronson, 2003; Jia, Strange, Wu, Collado, & Guan, 2006), length of residence in an L2-speaking environment, and relative L1:L2 usage (Flege, 1999, 2002; Flege & MacKay, 2004). Based on these assumptions, it follows that early bilinguals who have used their L2 so extensively that they have become L2-dominant should be the most likely to have developed L2 categories because they have strong L2 biases on all of these factors.…”
Section: Introductionmentioning
confidence: 99%